PM2.5 Concentrations Indoors and Outdoors in Heavy Air Pollution Days in Winter. (2015) - Song, Peiyao; Wanga, Lixin; Hui, Yang; Li, Rui
Abstract: The epidemiological studies have indicated that PM2.5 can increase morbidity and mortality, damage the respiratory system and the cardiovascular system, and affect the immune function. The objectives of this study are to understand PM2.5 pollution status in the households when the heavy air pollution occurs in the winter and the correlation of indoor PM2.5 pollution with outdoor, and to find out the effect of indoor human activities on the changes of indoor PM2.5 concentrations. Indoor PM2.5 concentrations were measured using CLH-2000 portable PM2.5 detector in the four households in December 7-8, 2013. When sampling indoors, the pattern of activity questionnaire was completed. The results showed that the average of indoor PM2.5 concentration is in the range of 112-416 μg/m 3, and the pollution level is more serious at 4 homes in Beijing in winter. Outdoor pollution, human activities and behaviors are the sources of indoor PM2.5 at homes. Human activities (cooking, smoking and cleaning) have more contribution to indoor PM2.5 than outdoor pollution. In general, the effect of indoor human activities on PM2.5 concentration is stronger than outdoor pollution and air cleaner.